Improvement of Asthma and Gastroesophageal Reflux Disease with Oral Pulvis stomachicus cum Belladonna, a Combination of Matricaria recutita, Atropa belladonna, Bismuth, and Antimonite: A Pediatric Case Report. Issue 1 (1st January 2016) - Von Schoen-Angerer, Tido; Madeleyn, René; Kiene, Helmut; Kienle, Gunver S.; Vagedes, Jan
The association between gastro-esophageal reflux disease (GERD) and asthma, although well established in adults, is less strong in the pediatric age group. Benefits of proton pump therapy are limited across age ranges. While there is a growing body of literature on the use of complementary treatments for both asthma and GERD, few studies have focused on treatment benefits for the GERD-asthma association. We present the case of a 2-year-old boy with asthma and GERD who was not responding to inhaled, low-dose corticosteroids, beta-mimetic therapy, and a 6-week course of proton pump inhibitor treatment. We noted a gradual disappearance of symptoms when he was given an oral preparation of Pulvis stomachicus cum Belladonna, an anthroposophic medication containing Matricaria recutita, Atropa belladonna, bismuth, and antimonite. Matricaria recutita and bismuth have known gastric protective properties, and Atropa belladonna contains anticholinergic agents that have a bronchodilatory effect. These complementary medications appear promising in terms of relieving the symptoms of GERD-associated asthma.